Responses to the film, "The Exorcist" (Module II, 2013)
United Kingdom. Footage of the film, "The Exorcist"; An American film described variously as "evil", "spurious" and "brilliant" which was nominated for ten Academy Awards.The clip includes a scene from the film, and Visnews reporter Tim Arlott speaking to filmgoers leaving a London theatre after a showing of "The Exorcist". Their reactions were generally favourable; one man said the film deserved all the Oscar nominations; a woman described the film as "sick", and said it should not be shown to the general public.Filmgoers are reported to have fainted and vomited in theatres throughout the United States, but a more sober reaction was reported in Britain.